Exploring the effect of emerging adults’ perceived stress on their psychosocial wellbeing in the context of the parent-adult child relationship - Patel, Priyanka Jayantibhai (Kansas State University, 2023)
The current study explores the longitudinal impact of perceived stress on emerging adults’ psychosocial wellbeing in the context of the parent-adult child (n= 323) relationship. To examine the longitudinal relationship, structural equation modeling was executed to study the direct and indirect effect of parents’ bioecological factors (i.e., marital satisfaction, social support, personality), young adults’ perceived stress, parenting, and young adults’ characteristics (i.e., purpose in life and sense of autonomy) on young adults’ psychosocial wellbeing. The pathways in this study’s model were guided by two theoretical frameworks: Belsky’s parenting model and family stress theory. Overall results revealed the direct influence of young adults’ perceived stress, purpose in life, and parental support on their psychosocial wellbeing. Future research suggestions and implications for practitioners working with young adults and parents are discussed.
Keywords: Parents’ bioecological context; Perceived stress; Parenting; Emerging adults’ characteristics; Emerging adults’ psychosocial wellbeing